Analisis Rasio Penerimaan dan Biaya Pada Usaha Pembesaran Ikan Beronang (Siganus sp.) Kelompok Tani Tambak Nusantara Kelurahan Guntung Kecamatan Bontang Utara Kota Bontang - Oky Syafruddin; Dayang Diah Fidhiani; Erwan Sulistiwanto (2339-1324, 2014)
This study was conducted from April to November 2013. Location of the study in Urban Village Guntung on Kelompok Tani Tambak Nusantara North Bontang. The total costs incurred in the fish rearing business beronang in Kelompok Tani Tambak Nusantara 1 times in the harvest (6 month) that each Rp. 20,262,500 – 24,989,000 the average of Rp. 23,563,785.7. Total effort expended in the production of fish rearing beronang in Kelompok Tani Tambak Nusantara 1 times in the harvest (6 month) that each Rp. 6,500,000 – 20,000,000 the average of Rp. 12,242,857. Receipt issued in fish rearing business beronang in Kelompok Tani Tambak Nusantara 1 times in the harvest (6 month) ranged between Rp. 6,500,000 – 20,000,000 the average of Rp. 12,242,857. Value R / C ratio of fish rearing business beronang in Kelompok Tani Tambak Nusantara 1 times in the harvest (6 month) ranged between 0.32 – 0.82 with an average 0.52 the values ​​show that the business is not profitable fish rearing beronang with R / C ratio <1.